Challenges facing Islamic Education in the Era of Globalization - Auliyaur Rokhim (Agrapana Media, 2026)
The main problem in this study is the lack of an integrative and comprehensive analysis of appropriate strategies to maintain the relevance and sustainability of Islamic education in the era of globalization. This study aims to analyze the challenges of Islamic education in the era of globalization and to examine strategic responses needed to strengthen its relevance and sustainability. The research employed a descriptive qualitative approach, using literature analysis and document review to explore contemporary issues related to Islamic education. The data were analyzed through thematic analysis, focusing on value integration, educator competence, curriculum relevance, and cultural influences. The results indicate that Islamic education faces major challenges in integrating Islamic values with modern knowledge, responding to global cultural influences, enhancing educators’ digital competencies, and developing relevant curricula. These challenges require comprehensive and adaptive strategies. The implications of this study suggest that Islamic education must undergo continuous transformation by strengthening value-based integration, improving educator quality, and designing future-oriented curricula to produce morally grounded and globally competitive graduates.